2005
DOI: 10.1093/toxsci/kfi086
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxin Fumonisin B1 Alters the Cytokine Profile and Decreases the Vaccinal Antibody Titer in Pigs

Abstract: Fumonisin B1 (FB1), a mycotoxin produced by Fusarium verticillioides, may contaminate feed and food. In the present study, we investigated the effect of FB1 on the modulation of the cytokine profile and on the establishment of a vaccinal antibody response. In vitro investigations on pig peripheral blood mononuclear cells (PBMC) indicate that FB1 decreased interleukin-4 (IL-4) and increased interferon-gamma (IFN-gamma) synthesis at both the protein and mRNA levels. A short in vivo exposure (7 days) of weanling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 37 publications
5
65
0
3
Order By: Relevance
“…It was also supposed, that the increased susceptibility of porcine pulmonary capillary endothelium to FB 1 (Gumprecht et al, 2001) may also contribute to the increased susceptibility to infectious and/or inflammatory diseases (Halloy et al, 2005), which was supported in the present study. Some other studies have also confirmed the pro-inflammatory effects of FB 1 and contributed significantly to the explanation of these effects via some investigations on the cytokine profile of FB 1 exposed pigs (Taranu et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It was also supposed, that the increased susceptibility of porcine pulmonary capillary endothelium to FB 1 (Gumprecht et al, 2001) may also contribute to the increased susceptibility to infectious and/or inflammatory diseases (Halloy et al, 2005), which was supported in the present study. Some other studies have also confirmed the pro-inflammatory effects of FB 1 and contributed significantly to the explanation of these effects via some investigations on the cytokine profile of FB 1 exposed pigs (Taranu et al, 2005).…”
Section: Discussionmentioning
confidence: 80%
“…In this regard, a study of Ramos et al (2010) demonstrated that lung damages are much complicated in swine inoculated with PRRS virus, when the same are exposed additionally to FB 1 in the feed diet. The authors explained this deterioration of the disease by immunosuppressive effect of FB 1, supposed to be due to the accumulation of free sphingoid bases and a subsequent inhibition of lymphocytes proliferation (Taranu et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…34 Previous studies have shown that even low contamination levels of FB1 (10 ppm) can decrease the immune response in pigs as expressed by the significant decrease in antibody titers against Morbus Aujesky at days 21 and 35 postvaccination. 33 Another study found that feeding a diet containing 10 mg FB 1 per kilogram of feed, in combination with Bordetella bronchiseptica and toxigenic Pasteurella multocida serotype D infection, increased the incidence, extension, and severity of pulmonary lesions in pigs.…”
mentioning
confidence: 98%
“…Grain spoilage reduces the nutritional value of cereals, resulting in 5% losses of foodstuff in world. Although there are many species of toxigenic moulds, only a few mycotoxins, particularly those affecting cereals, are considered to be significant for humans (26).…”
Section: Introductionmentioning
confidence: 99%